Classical and Modern Thought on International Relations - Jackson, R. author. aut Link
XII, 209 p.
Keywords: In the tradition of the English School of International Relations theory, this project from Robert Jackson seeks to show how continuities in international politics outweigh the changes. The author demonstrates how the world is neither one of anarchy, as put forward by realists, nor is it a fully cosmopolitan order, as argued by those on the other side of the theoretical spectrum. Instead, it is a world of states who acknowledge a set of moral constraints that exists between them.